Estratégias do design para a sustentabilidade da embalagem - Marques, Inês Fernandes, 1991- (2016)
The main subject of this dissertation is packaging, which is an inescapable product in our society nowadays. Every product we consume daily is generally protected and sheltered by a package that visually represents the product – the main feature of packaging. This research aims to assess the importance of packaging today as well as its role in the past, while searching for ways to improve its qualities as a design project. From the sustainability’s perspective, packaging is a factor that must be observed in dealing with its production, use and disposal and that is precisely the point of view that it is explored within this dissertation: packages’ ability of being sustainable and matching more ecological design practices. The main goal of this research is being able to take advantage of the package and its qualities as a selling means and at the same time make it a product that doesn’t harm our planet and the environment. Although packaging is targeted to match trade and economic issues, environmental factors have been addressed more incisively, as those are one of the biggest problems about this matter: the disposal of the package generates the accumulation of waste after the product is consumed. That being said, the challenge is to produce sustainable packaging and also to redefine the concept of packaging itself. Therefore this research intends to look for the link between packaging and sustainability and how that linkage can add value to the trade market and also to our planet’s health and well-being